2002
DOI: 10.1172/jci15695
|View full text |Cite
|
Sign up to set email alerts
|

T cell activation causes diarrhea by increasing intestinal permeability and inhibiting epithelial Na+/K+-ATPase

Abstract: Inflammatory bowel disease (IBD) is associated with mucosal T cell activation and diarrhea. We found that T cell activation with anti-CD3 mAb induces profound diarrhea in mice. Diarrhea was quantified by intestinal weight-to-length (wt/l) ratios, mucosal Na+/K+-ATPase activity was determined and ion transport changes were measured in Ussing chambers. Anti-CD3 mAb increased jejunal wt/l ratios by more than 50% at 3 hours, returning to base line after 6 hours. Fluid accumulation was significantly reduced in TNF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…Thus, injection of mice with CD-4 mAb results in diarrhea that has been examined in great detail, lending additional information regarding the role of TNFα in the pathogenesis of inflammation associated diarrhea. 21,22 CD-4 mAb results in the production of TNFα, and data supports the probability that the changes in ion transport in these animals are due to TNFα. The observed changes include decreases in NHE3 mRNA and protein, failure of aldosterone to increase the β and γ subunits of ENaC, Na,K-ATPase activity as well as decreasing mucosal permeability including increasing mannitol fluxes.…”
Section: Role Of Inflammationsupporting
confidence: 61%
“…Thus, injection of mice with CD-4 mAb results in diarrhea that has been examined in great detail, lending additional information regarding the role of TNFα in the pathogenesis of inflammation associated diarrhea. 21,22 CD-4 mAb results in the production of TNFα, and data supports the probability that the changes in ion transport in these animals are due to TNFα. The observed changes include decreases in NHE3 mRNA and protein, failure of aldosterone to increase the β and γ subunits of ENaC, Na,K-ATPase activity as well as decreasing mucosal permeability including increasing mannitol fluxes.…”
Section: Role Of Inflammationsupporting
confidence: 61%
“…Musch et al investigated the effect of acute T cell activation by anti-CD3 antibody on intestinal fluid loss in mice, and also studied EIPA (an inhibiter of Na + /H + exchange)-sensitive Na + absorption in the small intestine. 61 They observed an increase in enteropooling (fluid in the intestinal lumen), an increase in paracellular permeability, as well as a marked reduction in EIPA-sensitive Na + uptake, a reduced anion secretory response, and a decrease in Na + /K + adenosine 5 -triphosphate (ATP)ase activity, as early as 3 h after acute T cell stimulation. The same group demonstrated that interferon-␥ resulted in a decrease in expression and function of NHE3 and NHE2 in an intestinal cell line 6 h after exposure, and in rat intestine 48 h after injection.…”
Section: Electroneutral Nacl Absorptionmentioning
confidence: 98%
“…T cells secrete cytokines such as TNF-α and IFN-γ that modulate the epithelial barrier, by TJ disruption and by increasing the activity of MLCK, leading to subsequent cytoskeleton contraction. 52,53 These mechanisms could account for increased epithelial permeability; however, further studies are needed in order to identify the contribution of mucosal T lymphocytes to IBS pathophysiology.…”
Section: -Intestinal Perfusion Of An Isolated Intestinal Segment (Pegmentioning
confidence: 99%